Major Royal Jelly Protein 2 (mrjp2) Gene Detection in Apis dorsata Fabricius, 1793, Apis dorsata binghami Cockerell, 1906, Apis florea Fabricius, 1787, and Apis nigrocincta Smith, 1860 - Dewi, Yasinta; Purwanto, Hari (Universitas Gadjah Mada, 2024)
Indonesian people’s interest in honey, the product from honey bees, is quite high. It caused many cases of honey fraud such as mislabelling the entomological origin of honey. The Major Royal Jelly Protein 2 (mrjp2) gene, which encodes MRJP, can be used to determine the entomological origin of honey. The mrjp2 gene, for example, can be detected in honey from A. mellifera and A. cerana using species-specific primers for A. mellifera (MF-MR) and A. cerana (CF-CR). This study aims to detect the mrjp2 gene in several honey bee species native to Indonesia, namely A. dorsata, A. dorsata binghami, A. florea, A. nigrocincta, A. mellifera, and A. cerana as well as analyse the feasibility of MF-MR and CF-CR primers in determining the entomological origin of honey. The results showed that the MF-MR primers can amplify the DNA of A. dorsata binghami, A. florea, and A. mellifera, while CF-CR primers can amplify the DNA of both A. nigrocincta and A. cerana. The amplicons were subsequently sequenced. The phylogenetic tree and the genetic distance showed that there were differences and variation between each species of honey bee samples with the honey bee database. The data obtained from this research indicated that both primers could not determine the entomological origin of honey directly up to species level. The species level determination will only be possible using sequences information. However, in certain situations, the MF-MR and CF-CR primers were able to differentiate the honey bee species by including the information of the geographical origin of honey sample and the distribution area of each species of honey bees in Indonesia.